The influence of rural credit on the conservation of the Amazon biome - Alarcon Fernandes, Paulo Guilherme; Parré, José Luiz (Revista Brasileira de Estudos Regionais e Urbanos, 2026)
The advance of deforestation in the Amazon concerns society, while rural credit stimulates agricultural activity in the region. This study investigates the main drivers of deforestation and analyzes the effects of rural credit restrictions in the Amazon biome, as well as their potential to promote sustainability. Using the Geographically Weighted Regression (GWR) method for 2021, the results show that, in most municipalities, the relationship between deforestation rates, rural credit amounts, and cattle numbers was negative. This suggests that these variables contribute to forest preservation and highlights the effectiveness of Resolution 3545, which limits financial resources for agriculture linked to deforestation. In some areas, rural activities are supporting environmental preservation through the adoption of sustainable and organic farming practices. As a future research direction, the study recommends extending the time frame to capture longterm effects.